Path analysis of phosphorus dynamics and chili response to low rank coal-derived humic acid in P-deficient Inceptisols - Hermawan, Mega Kartika; Sofyan, Emma Trinurani; Sudirja, Rija; Nurbaity, Anne; Fitriatin, Betty Natalie; Mulyani, Oviyanti; Setiawati, Mieke Rochimi; Djuansah, Muhamad Rahman (Journal of Degraded and Mining Lands Management, 2026)
Jatinangor Inceptisols are formed from volcanic material with a high concentration of iron oxide and a low concentration of phosphorus (P), which leads to high rates of P fixation and low P fertilization efficiency. The situation is exacerbated by intensive agricultural practices. This research was conducted to assess the effect of humic acid derived from low rank coal (AHL) as a soil conditioner in enhancing P availability and chili response in P-deficient Inceptisols. The experiment was conducted in the greenhouse of the Soil Chemistry and Plant Nutrition Laboratory at Universitas Padjadjaran. AHL treatments were combined with various doses of SP-36 fertilizer to evaluate their direct and indirect effects on soil chemical properties, phosphate-solubilizing bacteria (PSB) populations, P uptake, and plant responses. The results showed that AHL application did not cause metal toxicity symptoms and significantly increased potential P, available P, cation exchange capacity (CEC), and total PSB populations. The best results were obtained with a combination of AHL at 30 kg ha?¹ and SP-36 at 125 kg ha?¹, which optimally enhanced P dynamics and chili yields. AHL was proven to reduce the need for inorganic P fertilizer by up to 50% without compromising chili yield or quality. These findings indicate that AHL has great potential to be developed as a locally sourced soil conditioner to support sustainable agriculture and the use of more environmentally friendly low-rank coal.